Desulfurization performance of choline chloride-based deep eutectic solvents in the presence of graphene oxide - Lim, C.Y. (MDPI AG, 2020)
Extractive catalytic oxidative desulfurization (ECODS) is the one of the recent methods used in fuel desulfurization which involved the use of catalyst in the oxidative desulfurization of diesel fuel. This study is aimed to test the effectiveness of synthesized choline chloride (ChCl) based deep eutectic solvent (DES) in fuel desulfurization via ECODS method, with the presence of graphene oxide (GO) as catalyst and hydrogen peroxide (H2O2) as oxidant. In this study, 16 DESs based on choline chloride were synthesized using glycerol (GLY), ethylene glycol (EG), tetraethylene glycol (TEG) and polyethylene glycol (PEG). The characterization of the synthesized DES was carried out via Fourier transform infrared spectroscopy (FTIR) analysis, density, and viscosity determination. According to the screening result, ChCl-PEG (1:4) was found to be the most effective DES for desulfurization using ECODS method, with a removal of up to 47.4 of sulfur containing compounds in model oil in just 10 min per cycle after the optimization of the reaction parameters, and up to 95 desulfurization efficiency could be achieved by six cycles of desulfurization. It is found that the addition of GO as catalyst does not increase the desulfurization performance drastically; hence, future studies for the desulfurization performance of DESs made up from ChCl and PEG and its derivatives can be done simply by using extraction desulfurization (EDS) method instead of ECODS method, for cost reduction purpose and easier regulation of DES waste into environment. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.